2018
DOI: 10.1177/1060028018795146
|View full text |Cite
|
Sign up to set email alerts
|

Abemaciclib: The Newest CDK4/6 Inhibitor for the Treatment of Breast Cancer

Abstract: Abemaciclib is an effective and well-tolerated treatment for HR-positive, HER2-negative advanced or metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…The Food and Drug Administration (FDA) has approved the CDK4/6 inhibitors Palbociclib, Ribociclib and Abemaciclib for treating metastatic breast cancer. These inhibitors have also demonstrated promising antitumor potentials both as a monotherapy and in combined therapy in numerous clinical trials [36]. CDK11 is a member of the serine/threonine protein kinase family.…”
Section: Introductionmentioning
confidence: 99%
“…The Food and Drug Administration (FDA) has approved the CDK4/6 inhibitors Palbociclib, Ribociclib and Abemaciclib for treating metastatic breast cancer. These inhibitors have also demonstrated promising antitumor potentials both as a monotherapy and in combined therapy in numerous clinical trials [36]. CDK11 is a member of the serine/threonine protein kinase family.…”
Section: Introductionmentioning
confidence: 99%
“…MONARCH 1, 2, and 3 clinical trials established Abemaciclib as an orally effective CDK4/6 inhibitor for HR+/HER2- advanced or metastatic breast cancer 72, 73.…”
Section: Discussionmentioning
confidence: 99%
“…CDK4 is a key member of the cell cycle-related subfamily,38 and it is reported to be involved in many physiological processes, including proliferation and apoptosis 39,40. In addition, CDK4 has been demonstrated to be regulated by post-translational modification of miR and acts downstream of multiple signaling pathways involved in cell proliferation and movement, and the carcinogenic effects of CDK4 have gradually emerged in some common human cancers, including BC 30,41,42. It was further observed that overexpression of CDK4 impaired the suppressive functions of miR-124 on BC cell viability, angiogenesis and proliferation in T24 cells and 5637 cells.…”
Section: Discussionmentioning
confidence: 99%